Rapid diagnosis of Mycobacterium marinum infection using targeted nanopore sequencing: a case report - Huang, Yan-Ying; Li, Qiu-Shi; Li, Zhao-Dong; Sun, Ai-Hua; Hu, Sheng-Ping (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium marinum (M. marinum) is a non-tuberculous mycobacterium (NTM) that can cause infectious diseases in aquatic animals and humans. Culture-based pathogen detection is the gold standard for diagnosing NTM infection. However, this method is time-consuming and has low positivity rates for fastidious organisms. Oxford Nanopore MinION sequencing is an emerging third-generation sequencing technology that can sequence DNA or RNA directly in a culture-independent manner and offers rapid microbial identification. Further benefits include low cost, short turnaround time, long read lengths, and small equipment size. Nanopore sequencing plays a crucial role in assessing drug resistance, clinical identification of microbes, and monitoring infectious diseases. Some reports on Mycobacterium tuberculosis (MTB) using nanopore sequencing have been published, however, there are few reports on NTM, such as M. marinum. Here, we report the use of nanopore sequencing for the diagnosis of M. marinum.